Effect of Antioxidant Vitamins on the Oxidant / Antioxidant Status in Patients with Multiple Sclerosis (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: multiple sclerosis; malondialdehyde; ascorbic acid; tocopherol